If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 23 = 4x + 173 Reorder the terms: 23 + 14x = 4x + 173 Reorder the terms: 23 + 14x = 173 + 4x Solving 23 + 14x = 173 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 23 + 14x + -4x = 173 + 4x + -4x Combine like terms: 14x + -4x = 10x 23 + 10x = 173 + 4x + -4x Combine like terms: 4x + -4x = 0 23 + 10x = 173 + 0 23 + 10x = 173 Add '-23' to each side of the equation. 23 + -23 + 10x = 173 + -23 Combine like terms: 23 + -23 = 0 0 + 10x = 173 + -23 10x = 173 + -23 Combine like terms: 173 + -23 = 150 10x = 150 Divide each side by '10'. x = 15 Simplifying x = 15
| 11-2x+8x+5=32 | | r+1/3=8/3 | | (x^2-2x)-180=0 | | 9=g+3 | | -(12-4x)+8(10-4x)= | | 34=t+15 | | x-5/3=10 | | 5(3x-4)+2=4(3x+2) | | 7+8x=98.2 | | -2/5y=-4/15 | | 15.99x-26.73=42.72 | | 0.05s+0.10(6000-s)=375 | | x+2=4(4x-6) | | 3x-5=1x-13 | | 7*0+8y=7 | | 6x^2+2x+2=150 | | 0.06p+0.08(1600-p)=65 | | -14=2x-8 | | 144.54=2.55h+73.14 | | .99k-27=42.72 | | -5x-10=14-3x | | -p=8 | | 2-x=-3x-4 | | 6p/5=8p-4/3 | | -480=-20(-6b) | | 3(2x-5)-4(5x-2)= | | -4x+5/11+3x-3/11=4/11 | | 11p-17p=12 | | 3(4x+5)-6= | | x^2+2x+1=2 | | 9r-18r=45 | | -2+9=5b-2-4b |